1976
DOI: 10.1016/0375-9474(76)90153-6
|View full text |Cite
|
Sign up to set email alerts
|

The (d, 6Li) reaction on 24Mg, 26Mg and 28Si at 35 MeV

Abstract: Data for the (d, eLi) reaction on targets of 24Mg, 2eMg and 2sSi have been obtained at 35 MeV bombarding energy. Angular distributions were measured for low-lying statesin the residual nuclei. Tern-range distorted-wave Born approximation (DWBA) calculations have been used to analyze the daJ_a_, The DWBA calculations account for the shapes of the experimental distributions reasonably well. The observation of significant population of unnatural parity states implies, however, that other transfer mechanisms may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…If the average experimental rather than theoretical relative ground-state e-spectroscopic factor is used together with the absolute value of 0.18, the value is S = 0.09. The average experimental value was obtained from the summary of Chung et al [1][2][3][4][5][6] which in-cludes studies of the reactions (6El, d) [7], (d, 6Li) [8], (e, 2~) [9] and (p, p c~) [10]. These values of 0.11 and 0.09 are in good agreement with the value S = 0.08 obtained from this study.…”
Section: T(o) ---T~]~~(o)supporting
confidence: 76%
“…If the average experimental rather than theoretical relative ground-state e-spectroscopic factor is used together with the absolute value of 0.18, the value is S = 0.09. The average experimental value was obtained from the summary of Chung et al [1][2][3][4][5][6] which in-cludes studies of the reactions (6El, d) [7], (d, 6Li) [8], (e, 2~) [9] and (p, p c~) [10]. These values of 0.11 and 0.09 are in good agreement with the value S = 0.08 obtained from this study.…”
Section: T(o) ---T~]~~(o)supporting
confidence: 76%
“…Large S(a) value has been reported for the second o+ state at 6.44 Me V. 263 l For this o+ state, the quartet model by Arima et al 11 BJ has suggested a quartet structure excited from (sd) shell to (Pf) shell. However, in results of the present cluster-model calculation, the wave function of the second o+ state consists predominantly of (sd) 8 In Table 5-V, the a-pick-up spectroscopic factors of 24 Mg~2 0 Ne* +a are Table 5 In Table 5-VI, oscillator quantum components of five o+ levels obtained in Nmax=30 are shown in percentage.…”
Section: Summary On 20 Nementioning
confidence: 90%
“…3a) . Predictions based on the simplest SU(3) approximations seem to be in remarkably good agreement with experiment [36][37][38][39] and differ but little from those calculated with much more complicated shell-model wave functions a~. Some a-spectroscopic amplitudes for states of lfico and 2fic°excitation in s-d shell nuclei have been given in ref.…”
Section: Introductionmentioning
confidence: 54%
“…(39) . With q = 4, Q = 9, and (~,~) _ (82), for example, only the first term with Q" = 0 survives in eq.…”
mentioning
confidence: 99%